Shifting sands. (Economist, 2013)
The article reports on the decreasing sales of personal computers (PCs) and laptop computers in 2013 as technology for mobile phones and tablet computers increases to make larger computers less necessary. Topics include how declining sales have impacted the revenue of technology companies like Dell, Hewlett-Packard (HP), and Lenovo, HP chief executive officer Meg Whitman's plans for returning the company to profitability, and how the computer server industry has improved under new technology.